Cultura de segurança do paciente e predisposição à ocorrência de eventos adversos em unidade de terapia intensiva - Rodrigues, Francisco Carlos Pinto (2017)
The issues surrounding the safety culture (CS) and the occurrence of adverse events (AE) are contemporary themes that stand out, worldwide, in the scientific and educational scenario. The study aimed to evaluate the safety culture of the patient and predisposition to the occurrence of adverse events in an Intensive Care unit. This is a cross-sectional study carried out with nurses and nursing technicians working in Adult Intensive Care Units of four hospitals located in the Southern Region of Brazil. Data were collected between June 2015 and January 2016. A questionnaire containing sociodemographic and labor data from the population was used, the Safety Attitudes Questionnaire (SAQ) to evaluate the safety culture, and the Predisposing Scale for the occurrence of Adverse Events (EPEA). The data were organized in Epi-Info, version 6.4, with double independent typing and analysis in the Statistical Package for the Social Sciences (SPSS), version 18.0 for Windows, through descriptive and inferential statistics. The cut-off point for positive evaluation of safety culture was ≥ 75 points in all SAQ domains. For EPEA cut-off points, three percentages (<50, between 50 and 75 and> 75), respectively, low, moderate and high perception were used. 115 workers participated, of which 29 were nurses and 85 were nursing technicians. Predominated female workers, young adults (24 to 37 years), race self-referred white, married, with children and without specialization. Higher percentage of workers had an employment relationship and considered ICU work little exhausting. The internal consistency of the SAQ was 0.88 (with a range of 0.60 to 0.81 in the domains) and the EPEA was 0.94 (0.74 for structure and 0.93 for process). The SAQ score ranged from 47.2 to 96.5 (71.6 ± 12.0). There was a positive evaluation in the areas of team work climate (76 ± 15.5) and satisfaction at work (89.9 ± 10.8). The Hospital Management Perception domain obtained the lowest result (62 ± 21.0). In EPEA, the mean score of the difference between ideal and real in the Structure domain was 0.97 (± 0.55) and in the Process was 0.87 (± 0.62). In both domains, workers were classified with low perception for predisposition to the occurrence of adverse events (46.1% and 49.5%, respectively). There was an inverse correlation between safety culture and predisposition to the occurrence of adverse events. It is concluded that the workers know the appropriate means for the referral and communication of the EA and that the safety culture in the hospitals surveyed is still in the process of construction, with demands and needs to be met in the short, medium and long term. The involvement of management by patient safety can improve the work processes and communication between the team, making the workers make their practices safer.